Improving the water flow in pipelines using floating technique - Govindasamy, Inba Malar (2012)
Pipelines transportation is widely used regardless in any industry.Mostly,liquid and gases are sent using the transportation method through a pipe.Turbulent flow in pipeline causes friction drag and pressure drag which results in pressure drop and increases the operational cost by increasing the pumping power losses.Therefore,an effectivepipeline flow is needed in order to reduce the pressure drop by improving the drag reduction in the pipeline system.This research is executed to improve water flow by using the floating technique.Natural Rubber (cis-1, 4-polyisoprene)was selected as floating materials by considering its flexible nature and strength.The dimension of the fabricated floating equipment are, 17 stripes of natural rubber (cis-1, 4-polyisoprene) in length of 10cm,15cm and 20cm,width and thickness of 0.3cm and 0.1cm respectively.The rubber stripes suspended in pipeline by using aluminium made ring.10 different flow rates of water used to a 1.5 inch sized pipe.The variables of length are 10cm,15cm and 20cm.During the experiment,the pressure drop before and after using floating technique was recorded and used to calculate the percentage of drag reduction.The data was analysed further by plotting graphs of percentage of drag reduction versus Reynolds numbers.The floating technique is proven to reduce the pressure drop,pumping power losses and degree of turbulence by increasing the drag reduction in pipeline transportation.A significant reduction of drag in the turbulent flow of water with the fabrication of floating equipment was appraised with pressure drop reduction.The applied floating technique proved to redirect the turbulence flow to laminar flowby correcting the mechanism of turbulent flow.The maximum drag reduction obtained is from 27.80% to 26.18% which occurs at a pipe length of 1m by using the floating device with the length of 15cm and 20cm. These results were attained for the Reynolds number of 51059.94 and 64985.38.